Analysis of Oil Dielectric Strength Insulation on Oil Circuit Breakers Based on Service Life and Operating Frequency - Engla Harda Arya; Benriwati Maharmi; Mohammad Lutfi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
The electricity distribution breakdown can be caused the service life and operating frequency of Oil Dielectric Strength (ODS). Hence, it requires a study due to the spare part is difficult to find. This paper aims to test the ODS on Oil Circuit Breaker (OCB) of 13.8 kV aged between 29 to 43 years. The test used the ASTM D1816 standard to analyze the effect of oil life and circuit breaker operating frequency on the physical, color and strength of ODS. For the visual test used the ASTM D1524 standard. The color test based on the ASTM D1500 standard. From the test results, it can be seen that 6DN F1 was yellow-black in colors. The color level was from 0.5 to 6, which was a striking color difference. This happens because it had been operating for 3 years with a frequency of 2 manual open times and 11 trips with a large normal load of 206A. In the 8D F7 feeder, there was also a decrease in breakdown voltage, which was far from 45.6 kV to 9.7 kV. Therefore, the oil was declared failed due to below the minimum standard of 27 kV. Based the validity test, the six samples were still within the allowable limits based on ASTM D1816 with the range value being below 92%. This means that the six samples were valid.